GAMBARAN KADAR HEMOGLOBIN (Hb) DAN EFEK SAMPING PADA AKSEPTOR KB INTRA UTERIN DEVICE (IUD) DI KELURAHAN TELUK WILAYAH KERJA PUSKESMAS PURWOKERTO SELATAN TAHUN 2012 - Desy Yulita; Feti Kumala Dewi (Universitas Harapan Bangsa Purwokerto, 2012)
Background: In a lot of bleeding allows the use of anemia so that the IUD shouldbe examined to determine the level of hemoglobin anemia. The head of KIA spacepuskesmas South Purwokerto on February 8, 2012 told the IUD acceptors neverexamined the Hb level, complaints acceptor average experience vaginal dischargeafter using the IUD. Initial examination 3 respondents are anemic.Objective: To determine picture Hb levels and side effects of the IUD acceptors inthe Bay Village Puskesmas South Purwokerto in 2012.Method: quantitative descriptive, observational approach. The researchinstrument a questionnaire and examination sheet digital Hb levels. Thepopulation of all IUD acceptors as many as 64 respondents. Type of data:primary and secondary data, with sample using accidental sampling as much as44 respondents, data analysis using univariate analysis.Results: Overview of Hb levels in IUD acceptors in the Bay Village PuskesmasSouth Purwokerto in 2012 largely have anemia as many as 25 respondents(56.8%). Overview of side effects in IUD acceptors in the Bay Village PuskesmasSouth Purwokerto In 2012 as many as 29 respondents (65.9%) experiencedchanges in the menstrual cycle, 27 respondents (61.4%) experienced leukorea, 24respondents (54.5%) Disminorea experience, 21 respondents (47.7%) experiencedmenorarrgia and thread are missing, nine respondents (20.5%) experiencedspotting, 4 respondents (9.1%) had suspected PRP, as much as 2 respondents(4.5%) experienced amenorrhoea.Conclusion: Overview of Hb levels and side effects of the IUD acceptors in theBay Village Puskesmas South Purwokerto in 2012 largely have anemia andadverse effects on changes in the menstrual cycle. Keywords: Hemoglobin, adverse effects on IUD acceptors.